Social media and non-university teachers from a gender perspective in Spain - Ángela Martín-Gutiérrez; Elias Said-Hung; Jesús Conde-Jiménez (Springer, 2024)
Abstract Non-university teaching staff must use social media platforms (SMP) to update themselves on educational matters. This study aims to analyze how these teachers in Spanish non-university education, differentiating between men and women, value and use SMPs to update themselves in educational matters. A total of 463 Spanish teachers participated in this survey-type study. The results show that the perception of usefulness, responsible use, and the role of educational institutions and agents remains medium or low. At the descriptive level, differences between men and women are detected in the perceptions of the teachers surveyed, with female teachers having a more favourable perception of the usefulness, use, and role of social media assumed by the institutions in which they work professionally compared to male teachers. It is concluded that there are three profiles of non-university teachers according to the variables analyzed that do not show differences according to the sex of the teachers. The implications of this study help to propose actions that help improve the scenario by 1) increasing the training channels, 2) increasing the levels of educational innovation through SMP, 3) increasing the effectiveness of teaching-learning strategies, and 4) promoting of skills that contribute to greater use and perception of these scenarios for the training of teachers and students.